DESAIN PEMBELAJARAN STEM MEDIA KOTAK HOLOGRAM DI SD - Khazdirotun Rohmah; Dindin Abdul Muiz Lidinillah; Agnestasia Ramadhani Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning design is a guideline for learning implementation that is prepared before the learning process begins. STEM learning design is prepared with STEM learning stages namely Ask, Imagine, Plan, Create, and Improve. This research was conducted to describe the implementation of the hologram box media learning design in cycle 1. The research method used is EDR (Education Design Research), which has 3 stages, namely analysis and exploration, design and construction, evaluation and reflection. The implementation of STEM learning in cycle one was carried out at SDN Rawajaya 04 class V with a total of 26 students. The learning stages are in accordance with the STEM syntax, namely ask, imagine, plan, create, and improve. In the first cycle, there are several things that need to be considered as evaluation material for the next cycle. 1) In group division and class conditioning. 2) In the STEM learning stage, imagine, and revise related worksheets.